2008
DOI: 10.1016/j.ijsolstr.2007.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Weakly-singular, weak-form integral equations for cracks in three-dimensional anisotropic media

Abstract: Singularity-reduced integral relations are developed for displacement discontinuities in three-dimensional, anisotropic linearly elastic media. An isolated displacement discontinuity is considered first, and a systematic procedure is followed to develop relations for the displacement and stress fields induced by the discontinuity. The singularity-reduced relation for the stress is particularly important since it is in a form which allows a weakly-singular, weak-form traction integral equation to be readily est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…To obtain a set of governing integral equations for B , we employ the pair of weakly singular, weak-form displacement and traction integral equations developed by Rungamornrat and Mear [16]. When specialized to the BEM region B , these integral equations take the form…”
Section: Governing Equations For Bmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain a set of governing integral equations for B , we employ the pair of weakly singular, weak-form displacement and traction integral equations developed by Rungamornrat and Mear [16]. When specialized to the BEM region B , these integral equations take the form…”
Section: Governing Equations For Bmentioning
confidence: 99%
“…For anisotropic media, Xu [15] generalized the work of Xu and Ortiz [11] to allow treatment of isolated cracks, and Rungamornrat and Mear [16,17] generalized the work of Li et al [12] to obtain a SGBEM applicable to cracks in a finite domain. We remark that it has been demonstrated that the weakly singular SGBEM is capable of yielding highly accurate stress intensity factors with relatively coarse meshes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, for crack problems it is typical that t J = 0, and for this reason the term in (4) involving the stress fundamental solution could be dropped without substantive loss. Nonetheless, we choose to retain this term and demonstrate a process for its regularization; the purpose in doing so is to provide a basis to treat the displacement integral relation (3) which, while not of particular relevance to the current investigation for isolated cracks, is important to the development of a SGBEM for treatment of cracks in a finite domain (see Rungamornrat and Mear 2008a).…”
Section: Standard Integral Relations For Isolated Crackmentioning
confidence: 99%
“…However, his formulation was limited to an isotropic case and the implementation of those equations to solve half-space problems has not been recognized. The regularization procedure analogous to that used by Li [6] was extended to model cracks in a whole space and finite bodies [7,8] and to take into account the material anisotropy [13,14], but the extension for the case of a half-space has not been found. In the present study, the procedure used by [6,7,[13][14][15] is further generalized to derive a set of regularized integral equations for a half-space containing discontinuities and made of multi-field materials.…”
Section: Introductionmentioning
confidence: 99%